The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0253984
|View full text |Cite
|
Sign up to set email alerts
|

“We need our own clinics”: Adolescents’ living with HIV recommendations for a responsive health system

Abstract: Adolescents living with HIV comprise a significant patient population in sub Saharan Africa but are poorly retained in care with consequent increased mortality and morbidity. We conducted in-depth interviews with 25 adolescents living with HIV engaged in care from five clinics in Johannesburg regarding their recommendations for the healthcare system. Findings included advocating for adolescent clinics, recognizing the importance of clinic-based support groups, valuing the influence lay counselors have in provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
4
16
0
Order By: Relevance
“…Experiences of stigma, and acts of discrimination, exist within life contexts, as well as a larger web of socio-cultural experiences and inequities. For example, a recent systematic review found that poor health outcomes of adolescents living with HIV were related to anticipated stigma, internalized stigma and stigma experienced when accessing healthcare [16]. Similarly, a more comprehensive view of gender identities has increased, and studies have highlighted stigma experienced by cis-and transgender people [17,18].…”
mentioning
confidence: 99%
“…Experiences of stigma, and acts of discrimination, exist within life contexts, as well as a larger web of socio-cultural experiences and inequities. For example, a recent systematic review found that poor health outcomes of adolescents living with HIV were related to anticipated stigma, internalized stigma and stigma experienced when accessing healthcare [16]. Similarly, a more comprehensive view of gender identities has increased, and studies have highlighted stigma experienced by cis-and transgender people [17,18].…”
mentioning
confidence: 99%
“…The perception and internalization of HIV-related stigma, coupled with the lack of supportive social relationships from HCPs, can lead to increased substance use, decreased general psychological health, and decreased engagement in healthcare. ALHIV tend to have mental health challenges that impact negatively on adherence and retention in care and health systems that appreciate this reality may be more responsive to it [ 49 , 58 ]. ALHIV need more reliable care and HCPs have a unique opportunity to provide supportive, comprehensive care, and try to understand their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers were open about their lack of capacity to provide adolescent‐friendly services, which were either non‐existent or poorly implemented in HIV treatment facilities, as well as the non‐complementarity between school programs and adolescent HIV treatment programs. Lack of skilled staff to manage ALHIV and weak implementation of adolescent‐friendly services is a leading challenge in structural efforts to improve holistic adolescent HIV care services in LMICs [ 68 , 69 ]. The need to integrate the school needs of ALHIV into their treatment programs cannot be overemphasized.…”
Section: Resultsmentioning
confidence: 99%
“…The need to integrate the school needs of ALHIV into their treatment programs cannot be overemphasized. It is important to promote differentiated service delivery care for ALHIV with multi‐month prescription of ART for treatment stable ALHIV, individualized treatment plans for unstable patients, taking into consideration their school schedules [ 68 , 69 ]. Some countries in SSA lack national guidelines on treatment and care for ALHIV.…”
Section: Resultsmentioning
confidence: 99%